The Influence of Analgesic Self-Medication Education on the Knowledge of Hajj Pilgrims - Sugihantoro, Hajar; Rahmadinata, Yusril Dwi; Cholina, Safira Isnaini (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2481, 2023)
The self-medication of analgesic drugs by elderly prospective hajj pilgrims in Indonesia requires better education to enhance understanding of safe and rational drug use, thus reducing the risk of side effects. Therefore, the research aimed at providing education to increase the knowledge of prospective Hajj pilgrims. The purpose of this study is to analyze the effects of providing video education on the knowledge level of self-medication with analgesic drugs among prospective Hajj pilgrims in the city of Batu. This study is an pre-experimental research using a one-group pretest-posttest design on 21 prospective hajj pilgrims in the Batu District, Batu City. The sampling was conducted using a purposive sampling method. Data were obtained through questionnaires administered to respondents both before and after the intervention. The analysis of the impact of video education on the knowledge of prospective hajj pilgrims about self-medication with analgetic drugs was performed using the Wilcoxon signed-rank statistical test. After being given education, there was a significant increase in the respondents knowledge about self-medication with analgetic drugs, rising from 19.04% having good knowledge previously to 90.47% after the video education session, with the Wilcoxon test results indicating a significant difference between the pretest and post-test scores; the relatively low z-score (-3.794) and very low p-value (0.00) indicate that the ranking for the group with post-test scores is higher, signifying a significant improvement, thus post-test scores are better than pretest scores.